Automated Electronic System for Experiments with Stress Loadings by Hypergravitation - Přibil, J.; Frollo, I.; Kvetňanský, R.; Juráni, M. (Elektronika ir Elektrotechnika, 2007)
Equipment serves for implementation of series of experiments on small animals that are subjected by hypokinesis or hypergravitation during different time intervals. The instrumentation is equipped by telemetric control system for programmable blood collection using cannulation from experimental animals located in hypokinetic boxes or on a centrifuge. The goal of experiments is monitoring of an influence on blood properties during different gravitational overload values G, evaluation of hormone levels, neurotransmitters and metabolism. Results serve for evaluation of living organism ability to overcome the stress load. One set of the equipment consists of a transmitter and receiver equipped by microcomputers, 28 pairs of active rotor stepping motors, each driving two pairs of syringes. Transmitter and data signals receivers are active on frequency of 433,92 MHz using modulation ensuring high immunity towards malfunction. The equipment is controlled by computer equipped by interactive user-friendly program.